Bone isotopes, eggshell and turkey husbandry at Arroyo Hondo Pueblo. (December 2016) - Conrad, Cyler; Jones, Emily Lena; Newsome, Seth D.; Schwartz, Douglas W.
Abstract: Studies of archaeofaunal turkey and eggshell remains have identified a clear and consistent pattern of turkey husbandry across the prehistoric Southwest. Domestic turkeys appear to have been penned, fed maize, and kept genetically isolated from wild turkey populations. In this study we use carbon (δ 13 C) and nitrogen (δ 15 N) isotope values, scanning electron microscopy of eggshells, and quantitative analysis of turkey remains from Arroyo Hondo Pueblo (LA 12) to explore how turkey husbandry at this Pueblo IV site fits into the overall regional pattern. We find that although turkeys seem to have played a minor role in the overall faunal subsistence at Arroyo Hondo, they were nevertheless carefully husbanded, even during periods of climatic stress and human demographic fluctuation. Highlights: Bone isotopes of the Arroyo Hondo turkeys suggest a C4 -based diet. Turkey husbandry was stable despite climatic and demographic variability. Quantitative analyses suggest turkeys played a minor role in subsistence.